The Texan's surprise return - Navarro, Jolene (Navarro, Jolene. Cowboys of Diamondback Ranch., 2019)
For three years, Xavier De La Rosa<U+2019>s family thought he was dead. Now Xavier is back home in Texas for Christmas, and finds a wife he can<U+2019>t remember and adorable triplets he never knew existed. Can Xavier reclaim his memories and the love he left behind<U+2026>before he returns to the job that nearly killed him?